Some Fixed Point Results for TAC-Type Contractive Mappings - Sumit Chandok; Kenan Tas; Arslan Hojat Ansari (Journal of Function Spaces)
We prove some fixed point results for new type of contractive mappings using the notion of cyclic admissible mappings in the framework of metric spaces. Our results extend, generalize, and improve some well-known results from literature. Some examples are given to support our main results.